Direct electrocatalytic activity of chicken liver sulfite oxidase immobilized on binary self-assembled monolayer composed of separated domains having opposite charges - Phong, Pham Hong (Vietnam Journal of Chemistry, 2016)
In this work, the final binary SAMs composed of 11-aminoundecanethiol (AUT) domains and 10-carboxy-1-decanethiol (MUA) domains on In this work, the final binary SAMs composed of 11-aminoundecanethiol (AUT) domains and 10-carboxy-1-decanethiol (MUA) domains on Au(111) substrate was used for immobilizing chicken liver sulfite oxidase (CSO) to study the direct electron transfer and detect sulfite anions. Scanning tunneling microscope images clearly showed the phase separation between AUT and MUA domains in the final binary SAMs prepared by the electrochemically selective replacement method. The electrochemical signals of CSO appeared on the voltammogram indicated that the direct electron transfer between the enzyme and the modified electrode could be obtained without electron mediator. The electrocatalytic currents of sulfite oxidation by CSO immobilized on the final binary SAMs were linearly dependent on their concentrations in solution with R2 = 0.988, revealing a possibility in detection this anion by employing the bioelectrochemical sensor.